2016
DOI: 10.1177/0007650316675617
|View full text |Cite
|
Sign up to set email alerts
|

You Scratch My Back and I Scratch Yours: Investigating Inter-Partner Legitimacy in Relationships Between Social Enterprises and Their Key Partners

Abstract: Social enterprises, like almost all organizations, continuously strive for external legitimacy. To be perceived as externally legitimated by society, social enterprises often engage in strategic partnerships. However, scholars have only recently turned their attention to the legitimating function of such partnerships. The purpose of this article is to address the hitherto neglected construct of inter-partner legitimacy. Drawing on institutional theory, we hypothesize that such inter-partner legitimacy affects … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
41
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 29 publications
(41 citation statements)
references
References 107 publications
0
41
0
Order By: Relevance
“…Second, we contribute to the SE legitimacy literature by highlighting the importance of stakeholder engagement in legitimisation exercise. While past research discussed the conferral of legitimation by external actors (Weidner, Weber, and Göbel 2016), it had not sufficiently explored the specific ways in which SE actively engage with their stakeholders to legitimise their hybridity. Literature has shown that SEs have robust support systems as well as collectivism, as their effort to fit in (De Clercq and Voronov 2009; Aaboen, Dubois, and Lind 2013), nevertheless, little has been done in relation to enhancing our understanding of the collaborative activities that can help SEs acquire essential resources in order to stand out (Dart 2004).…”
Section: Discussionmentioning
confidence: 99%
“…Second, we contribute to the SE legitimacy literature by highlighting the importance of stakeholder engagement in legitimisation exercise. While past research discussed the conferral of legitimation by external actors (Weidner, Weber, and Göbel 2016), it had not sufficiently explored the specific ways in which SE actively engage with their stakeholders to legitimise their hybridity. Literature has shown that SEs have robust support systems as well as collectivism, as their effort to fit in (De Clercq and Voronov 2009; Aaboen, Dubois, and Lind 2013), nevertheless, little has been done in relation to enhancing our understanding of the collaborative activities that can help SEs acquire essential resources in order to stand out (Dart 2004).…”
Section: Discussionmentioning
confidence: 99%
“…The relational view thereby offers a more differentiated evaluation of partnerships in the NFP sector than previous perspectives have. Lastly, our study is one of the few to add to the very small body of literature that empirically proves several determinants of the relational view within one model (Weber et al, ).…”
Section: Discussionmentioning
confidence: 93%
“…Beyond the mutually created social impact, both parties may experience an increased legitimacy that relevant stakeholder groups attribute to them. Such additional benefit is arguably an important motive for establishing inter‐organizational relationships in the NFP sector (Dacin, et al, ; Herlin, ; Rueede and Kreutzer, ; Weidner et al, ). Our study thus adds to the rare empirical dyadic investigations on the question of which partner, if either, benefits from particular types of resources when complementary resources are exchanged (Jamali and Keshishian, ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Collaborative networking is influential in SE success, and their ability to connect and support one another increases knowledge, capacity and income streams (Jenner, 2016;Weidner, Weber and Gobel, 2016). Jenner (2016) however, posits that the pursuit of commercial viability and growth results in a landscape where SEs are now competing as opposed to collaborating.…”
Section: Delphi Issue: 'Finance'mentioning
confidence: 99%